If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -3(3n + -2) = 0 Reorder the terms: 12 + -3(-2 + 3n) = 0 12 + (-2 * -3 + 3n * -3) = 0 12 + (6 + -9n) = 0 Combine like terms: 12 + 6 = 18 18 + -9n = 0 Solving 18 + -9n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + -9n = 0 + -18 Combine like terms: 18 + -18 = 0 0 + -9n = 0 + -18 -9n = 0 + -18 Combine like terms: 0 + -18 = -18 -9n = -18 Divide each side by '-9'. n = 2 Simplifying n = 2
| 9x-5=-x+25 | | 3x+12=2x+52 | | (8rs-t)-(6t+5rs)= | | 2x=8x-18 | | 8c+16=5c-1 | | 6-x+12=10+7 | | x+5=2x-13 | | 1/4(p-30 | | 3z=9z-18 | | (3a-2cd)-(2b+3cd)= | | 5G+21=11g | | 0.06x+0.03y=27 | | 0.06x+0.03y=277 | | log(x^3-11x)-logx=2 | | 2y=4y-6 | | Y=-16x+80x | | (a^3-2a^3)-(3a^2-4a^3)=equation | | 25x-1=625 | | -3x-5(5x+13)=78 | | 4y-1=25 | | 2x+2=-1x+26 | | ((m^6n)^-2(m^2n^-2)^3)/m^-1n^-2 | | 9x+4=-18 | | 2/4p=3/4p+2 | | 15/17-2/34 | | 40=6x+16 | | R(4)+8= | | 10=6x+16 | | 15x+20x=1800 | | 1.8+32=90 | | -8y+8=37x-7 | | -3(5x+-4)=21 |